High Molecular Weight ACTH-Precursor Presence in a Metastatic Pancreatic Neuroendocrine Tumor Causing Severe Ectopic Cushing's Syndrome: A Case Report - Mehta, Roopa; Lam-Chung, César Ernesto; Hinojosa-Amaya, José Miguel; Roldán-Sarmiento, Paola; Guillen-Placencia, Maria Fernanda; Villanueva-Rodriguez, Gerladine; Juarez-Leon, Oscar Alfredo; Leon-Domínguez, Jefsi; Grajales-Gómez, Mariana; Ventura-Gallegos, Jose Luis; León-Suárez, Andrés; Gómez-Pérez, Francisco J.; et al. (Frontiers in Endocrinology, 2020)
Ectopic ACTH-secretion causing Cushing’s syndrome is unusual and its diagnosis is frequently challenging. The presence of high-molecular-weight precursors throughout pro-opiomelanocortin (POMC) translation by these tumors is often not reported. We present the case of a 49-year-old woman with a three-month history of proximal muscular weakness, skin pigmentation, and weight loss. Upon initial evaluation, she had a full moon face, hirsutism, and a buffalo hump. Laboratory workup showed hyperglycemia, hypokalemia and metabolic alkalosis. ACTH, plasma cortisol and urinary free cortisol levels were quite elevated. Serum cortisol levels were not suppressed on dexamethasone suppression testing. An octreo-SPECT scan showed enhanced nucleotide uptake in the liver and pancreas. Transendoscopic ultrasound-guided biopsy confirmed the diagnosis of a pancreatic ACTH-secreting neuroendocrine tumor (NET). Surgical excision of both pancreatic and liver lesions was carried out. Western blot analysis of the tumor and metastases revealed the presence of a high-molecular-weight precursor possibly POMC (at 30 kDa) but not ACTH (normally 4.5 kDa). ACTH-precursor secretion is more frequent in ectopic ACTH-secreting tumors compared with other causes of Cushing’s syndrome. Hence, the measurement of such ACTH precursors warrants further evaluation, especially in the context of ACTH-dependent hypercortisolism.